2023
DOI: 10.1515/med-2023-0752
|View full text |Cite
|
Sign up to set email alerts
|

SMOC2 plays a role in heart failure via regulating TGF-β1/Smad3 pathway-mediated autophagy

Abstract: Heart failure (HF) is a major global cause of morbidity and mortality. This study aimed to elucidate the role of secreted protein acidic and rich in cysteine-related modular calcium-binding protein 2 (SMOC2) in HF development and its underlying mechanism. Using a rat HF model, SMOC2 expression was examined and then knocked down via transfection to assess its impact on cardiac function and damage. The study also evaluated the effects of SMOC2 knockdown on autophagy-related molecules and the transforming growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…SPARC-related modular calcium-binding protein 2 (SMOC2), part of the SPARC family of matricellular proteins, is known to promote endothelial cell proliferation, migration, and angiogenesis 32 . Research indicates that SMOC2 expression escalates in rats experiencing heart failure, and silencing SMOC2 can mitigate heart failure symptoms by modulating autophagy via the TGF-β1/Smad3 signaling pathway 33 . Additionally, mouse studies have demonstrated that SMOC2 knockdown can ameliorate cardiac function impairment and cardiac fibrosis, potentially through the inhibition of the ILK/p38 signaling pathway 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPARC-related modular calcium-binding protein 2 (SMOC2), part of the SPARC family of matricellular proteins, is known to promote endothelial cell proliferation, migration, and angiogenesis 32 . Research indicates that SMOC2 expression escalates in rats experiencing heart failure, and silencing SMOC2 can mitigate heart failure symptoms by modulating autophagy via the TGF-β1/Smad3 signaling pathway 33 . Additionally, mouse studies have demonstrated that SMOC2 knockdown can ameliorate cardiac function impairment and cardiac fibrosis, potentially through the inhibition of the ILK/p38 signaling pathway 34 .…”
Section: Discussionmentioning
confidence: 99%
“…SPARC-related modular calcium-binding protein 2 (SMOC2), part of the SPARC family of matricellular proteins, is known to promote endothelial cell proliferation, migration, and angiogenesis 32 . Research indicates that SMOC2 expression escalates in rats experiencing heart failure, and silencing SMOC2 can mitigate heart failure symptoms by modulating autophagy via the TGF-β1/Smad3 signaling pathway 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor (TGF) is a cytokine with numerous functions that regulates and takes part in a variety of biological and pathological events in the heart. Saljic et al (2022) , Gu and Liang, (2023) , Liang et al (2022) , Ren et al (2023) , Alex et al (2023) , Dong et al (2023) . To protect the heart, the TGF-β signaling system controls apoptosis, autophagy, and antifibrotic activities ( Deng et al, 2019 ; Shen et al, 2020a ; Liang et al, 2022 ).…”
Section: Cardiovascular Disease-related Signal Pathwaysmentioning
confidence: 99%